Open smart city view: uma solucção computacional para manipulação e apresentação de dados governamentais - Lusa, Diego Antonio (2016)
The smart citizen, in the exercise of its duties front of smart city, empowers itself through the information it has at its disposal. Among the available informations sources are the open government data. However, such data is made available to society in its raw state and in di erent places, which impose certain dificulties in its consumption. In view of this, the present work introduces the Open Smart City View architecture, an architectural framework that aggregates data integration techniques and data warehousing to give conditions to integrated and simpli ed view of information coming from open government data sets collected from various sources. Divided into four functional layers, the architecture presents itself as an empowerment tool that abstracts the technical aspects associated with the collection and use of data sets while maintaining the focus of the citizens' understanding of the information extracted. Thus, the architecture is consistent with the greater empowerment of citizens through quality information, corroborating directly with the open data and public transparency initiatives, as well as with the consolidation of the smart citizen profile.